PROFIL PEMECAHAN MASALAH MATEMATIKA MAHASISWA MENGGUNAKAN LANGKAH POLYA BERDASARKAN GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD DEPENDENT - Tyas, Dewi Kristika Findia Ning (Media Pendidikan Matematika, 2018)
Based on the experience of the researchers taught the subject of Economic Mathematics many students who have not been able to solve the problem solving. One alternative that can be used to solve the problem is by using Polya steps. When solving a mathematical problem, each student has a different way of thinking. The difference is possible because of differences in student cognitive style. The cognitive styles used in this research are Field Independent cognitive style and Field Dependent cognitive style. The material chosen in this research is the demand function, the Bid Function, the Savings Function and the Taxation Function. This research is a descriptive research with qualitative approach which aims to describe the problem solving ability of student mathematics using Polya steps in terms of cognitive style of FI and FD. Subjects in this research are students of VI semester of Mathematics Education Program. Technique of taking research subject is by purposive sample. The results showed that FI subject understood the problem well. In the planning step, the FI subject can analyze the information received. Subjects use previously learned information and solve problem-solving given to the problem as planned and check back on each question. The subject of FD can not receive information and understand the problems that exist in the problem and can not process information/do not understand the purpose of the problem. In the planning step, the subject of FD is unable to think how to solve the problem and is not accustomed to rechecking